Psychological Mechanisms of Athlete Achievement: A Systematic Thematic Overview of the Interactions Between Social Support, Self-Efficacy, and Achievement Motivation - Natalia Irandah; Sucipto; Burhan Hambali (Tadulako Journal Sport Sciences And Physical Education, 2025)
Achievement motivation is fundamentally a key driver behind an athlete's resilience, hard work on the field, and overall competitive success. While previous research has often explored social support and self-efficacy as separate pieces of the puzzle, there is a marked lack of a big-picture synthesis that maps how the three interrelate and work together. To bridge this gap, this study systematically outlines the triad of relationships between social support, self-efficacy, and achievement motivation in athletes. Following PRISMA 2020 guidelines, a systematic thematic review of the literature was conducted across three major databases—Scopus, Google Scholar, and ResearchGate—with Zotero and Microsoft Excel handling reference management and data synthesis. Of the 3,630 initial search results, 15 empirical papers published between 2020 and 2025 were selected. The synthesized data revealed that self-efficacy stood out as a key predictor of achievement motivation, accounting for 43.4% to 75.7% of the variance across the thematically reviewed literature. Furthermore, social support from parents, coaches, teammates, and peers consistently increases an athlete's drive to succeed. This external support operates directly or indirectly through key mediators such as self-efficacy and psychological resilience. Ultimately, having a solid support system serves as a crucial environmental asset that anchors athletes' self-confidence, keeps them persistent, and strengthens their commitment to long-term achievement metrics. Moving forward, these insights suggest that sport development frameworks should focus more than just physical training; they need to intentionally build structured social support networks and implement targeted self-efficacy interventions to truly optimize athlete motivation and achievement metrics.